The moral primacy of the human being. Issue 9 (6th August 2010) - Parker, C
Abstract : Can the view that medical science is more important than the individual properly persuade recruitment to trials? This paper considers the nature and interests of the person and their relationships to the concepts of science and society; and analyses a conception of value used to balance the interests of science and research subjects. The implications of arguments opposing the primacy of the individual are set out to indicate their implausibility; while the primacy principle is described to show its necessity in any moral society. Finally, the importance of fully informed consent to participate is explained with the requirement that the individual human life provide the criteria of moral value for human life.